Comorbidity, Treatment, and Service Utilization Patterns in Difficult-to-Treat Depression Patients: A Retrospective Study in a Portuguese Community Mental Health Team - João Gouveia; Marta Moura Neves; Nuno Madeira; Vítor Santos; António Macedo (Medicina)
Background and Objectives: Observational studies with data from real-world clinical practice with patients with difficult-to-treat depression (DTD) are rare. This study aims to collect observational data from the real-world clinical practice of a Portuguese community mental health team (CMHT) on the prevalence of DTD and to explore differences between DTD and non-DTD groups. Materials and Methods: We conducted a retrospective chart review study using data from Electronic Health Records (EHRs) of adult patients with psychiatric disorders followed by a CMHT from the Department of Psychiatry of the Coimbra Local Health Unit (between 1 December 2020–31 December 2022). The Dutch Measure for quantification of Treatment Resistance in Depression (DM-TRD) was used to assess the degree of treatment resistance and the Charlson Comorbidity Index (CCI) to measure medical comorbidity. Results: A quantity of 473 patients were referred to Cantanhede CMHT for a first assessment. Of these, 219 patients met the criteria for a primary diagnosis of any depressive disorder. Assistant psychiatrists identified 57 patients with DTD during follow-up (approximately 26%). The DTD group had higher rates of depressive episodes, greater depression severity, increased service use, higher DM-TRD scores, and a higher prevalence of comorbid anxiety symptoms, personality disorders, and severe medical comorbidities. The DTD group also had a higher prescription rate of antidepressants. Differences were observed in the use of antidepressant augmentation strategies and in the prescription of anticoagulant/antiplatelet drugs and analgesics, with higher prescription rates in the DTD group. We found correlations between DM-TRD and CCI scores, and between DM-TRD scores and all service use variables. Conclusions: Our results are consistent with a similar study in the United Kingdom, highlighting the need for a different approach to the management of DTD patients, who continue to live with a significant burden despite usual pharmacological and non-pharmacological treatments.